Association between the Size of Humeral Head Cysts and the Extension of Rotator Cuff Tears - Promsang, MD, Trai; Kuptniratsaikul, MD, Somsak; Kongrukgreatiyos, MD, Kitiphong; Phaisinsomboon, Monchaya (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To evaluate the association between the size of humeral head cysts and the number of rotator cuff tears. Methods: A retrospective study of 115 patients who had a diagnosis of rotator cuff tear by magnetic resonance imaging (MRI) were reviewed and analyzed. The diameters of the cysts were measured using a calibrated digital caliper. Pearson’s correlation test was used to identify the correlation between the number of rotator cuff tears and the diameter of cysts. Results: A total of 115 shoulder MRIs from 115 patients were included in the present study. The average diameter of cysts was 6.7±2.9 mm. The average diameter of cysts for the group of one, two and three rotator cuff tendon tears was 6.2±3.0, 7.2±2.7, and 7.8±2.9 mm, respectively. There was no statistically significant difference of cyst diameters between the groups of rotator cuff tears. There was no statistically significant correlation between cyst diameters and the number of rotator cuff tears (r = 0.2, P = 0.1). Conclusion: There was no correlation between the number of rotator cuff tears and cyst size. However, we observed a trend in which the cyst size was slightly larger when the number of tendon tears increase. This finding indicated that the diameter of subchondral bone cysts might be greater in patients with massive rotator cuff tears. Large humeral head cysts may cause unsecure fixation for suture anchor placement. The orthopaedic surgeon must be aware of and prepare for large subchondral bone cysts during the arthroscopic rotator cuff repair.